2018
DOI: 10.12809/hkmj187215
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on the management of familial hypercholesterolaemia in Hong Kong: an expert panel consensus viewpoint

Abstract: In 2016, meetings of groups of physicians and paediatricians with a special interest in lipid disorders and familial hypercholesterolaemia were held to discuss several domains of management of familial hypercholesterolaemia in adults and children in Hong Kong. After reviewing the evidence and guidelines for the diagnosis, screening, and management of familial hypercholesterolaemia, consensus was reached on the following aspects: clinical features, diagnostic criteria, screening in adults, screening in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The potential role of elevated Lp(a) in risk stratification has been acknowledged in some guidelines on the management of HeFH [135][136][137], but in not in others [50,138,139] (Table 3). Once an efficient treatment of elevated Lp(a) becomes widely available, there will be a requirement not only for risk estimation including the Lp(a)-specific contribution to total CV risk, but also for guiding the clinicians to properly monitor the efficacy and safety of the treatment of elevated Lp(a).…”
Section: Towards New Clinical Practice Guidelinesmentioning
confidence: 99%
“…The potential role of elevated Lp(a) in risk stratification has been acknowledged in some guidelines on the management of HeFH [135][136][137], but in not in others [50,138,139] (Table 3). Once an efficient treatment of elevated Lp(a) becomes widely available, there will be a requirement not only for risk estimation including the Lp(a)-specific contribution to total CV risk, but also for guiding the clinicians to properly monitor the efficacy and safety of the treatment of elevated Lp(a).…”
Section: Towards New Clinical Practice Guidelinesmentioning
confidence: 99%
“…In 2016, Zhou and Zhao reviewed studies of FH in Asian populations 30) . The authors found that In the Asia Pacific region, specific FH guidelines have been published for Australia and New Zealand 34,35) , China 36) , Hong Kong 37) , and Japan 38,39) . Table 3 provides a summary of the key recommendations made in these guidelines regarding diagnosis, treatment, and cascade screening.…”
Section: Fh Care Gap In Asia Pacificmentioning
confidence: 99%
“…Summary of key recommendations of specific FH guidelines in the Asia Pacific region[34][35][36][37][38][39] …”
mentioning
confidence: 99%
“…Clinical criteria have often been used for the diagnosis of FH [7][8][9]. These include the Simon Broome Register Group criteria, the Make Early Diagnosis to Prevent Early Deaths (MEDPED) criteria, and the Dutch Lipid Clinic Network criteria.…”
Section: Diagnosis Of Familial Hypercholesterolemiamentioning
confidence: 99%